(untitled) (New York, 1941)
This book introduce the role of war in the development of Japanese capitalism. The reorganization of the Japanese economy factors and trends, some basic problems of Asiatic contitental development...
Keywords: Công nghiệp,Industries; Nhật Bản,Japan